2020
DOI: 10.1088/1681-7575/abbdbf
|View full text |Cite
|
Sign up to set email alerts
|

The comparability of the determination of the molar mass of silicon highly enriched in 28Si: results of the CCQM-P160 interlaboratory comparison and additional external measurements

Abstract: An international comparison study on the accurate determination of the molar mass M(Si) of silicon artificially enriched in 28Si (x(28Si) > 0.9999 mol mol−1) has been completed. The measurements were part of the high level CCQM-P160 pilot study assessing the ability of National Metrology Institutes (NMIs) and Designated Institutes (DIs) to make such measurements at the lowest possible levels of measurement uncertainty and to identify possible difficulties when measuring this kind of sample. This study supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In the first test system, the sample solutions, x, consisted of aqueous TMAH ( w (TMAH) = 0.0006 g/g) as the matrix with traces of the analyte: silicon with natural isotopic composition. The sample solutions were taken from a study described in [ 29 ]. There, the aqueous TMAH served as a blank solution for the measurement of isotope ratios of enriched silicon samples.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first test system, the sample solutions, x, consisted of aqueous TMAH ( w (TMAH) = 0.0006 g/g) as the matrix with traces of the analyte: silicon with natural isotopic composition. The sample solutions were taken from a study described in [ 29 ]. There, the aqueous TMAH served as a blank solution for the measurement of isotope ratios of enriched silicon samples.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…Briefly, the TMAH sample solutions were prepared by dissolving highly concentrated ( w (TMAH) = 0.25 g/g), electronic grade (99.9999%) TMAH from Alfa Aesar™ (Thermo Fisher (Kandel) GmbH, Germany) in highly purified water (resistivity = 18 MΩ cm), the latter prepared using a commercial water purification system (Merck Millipore™, Burlington, MA, USA). All solutions were prepared and stored in precleaned labware (perfluoroalkoxy copolymer PFA) according to a protocol given in [ 29 ]. The spike solutions, y, originated from chemically pure silicon single crystals highly enriched in 30 Si dissolved in aqueous TMAH, whereas reference material z was prepared from well-characterized silicon crystals (material code: WASO04) with known natural-like isotopic composition [ 30 ].…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…In order to further increase the accuracy of the measured molar mass, ultra-enriched 28 Si crystals (with much lower 29 Si and 30 Si abundance compared to the AVO28 material) were produced, and an international comparison study to determine the molar mass was organized by Physikalisch-Technische Bundesanstalt (PTB, Germany). 6 Two techniques have been used to measure isotopic compositions: the traditional gas isotope ratio measurement, and, the 'virtual element' isotope dilution mass spectrometry (VE-IDMS). These two techniques produced internally consistent results within each technique respectively, 4,7,8 while large discrepancies were found between the different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…2011, Rienitz et␣al . 2020). Because large variations of Si isotopic composition in normal terrestrial materials were observed and thus the uncertainties of the Si isotopic composition and its atomic weight could not be reduced, the Commission on Isotopic Abundances and Atomic Weight of the International Union of Pure and Applied Chemistry (IUPAC) has changed the isotope abundances of Si to the interval [0.92191, 0.92318] ( 28 Si), the interval [0.04645, 0.04699] ( 29 Si) and the interval [0.03037, 0.03110] ( 30 Si), respectively, and the corresponding atomic weight to the interval [28.084, 28.086] (Wieser et␣al .…”
mentioning
confidence: 99%
“…As one of the important sources of oceanic silicon, much attention has been attracted by dissolved Si, which greatly affects the growth of diatoms in coastal areas, contributing to global carbon fixationan important process proved to be affected by weathering and biological factors (Tréguer and Rocha 2013, Weiss et al 2015, Frings et al 2016, Zhang et al 2020. What is more, as one of the two ways to redefine the SI (International System of Units) unit of mass, the kilogram, silicon isotope ratio measurement has played an important role in the determination of the Avogadro constant (De Bièvre et al 1995, Rienitz et al 2020. Because large variations of Si isotopic composition in normal terrestrial materials were observed and thus the uncertainties of the Si isotopic composition and its atomic weight could not be reduced, the Commission on Isotopic Abundances and Atomic Weight of the International Union of Pure and Applied Chemistry (IUPAC) has changed the isotope abundances of Si to the interval [0.92191, 0.92318] ( 28 Si), the interval [0.04645, 0.04699] ( 29 Si) and the interval [0.03037, 0.03110] ( 30 Si), respectively, and the corresponding atomic weight to the interval [28.084, 28.086] (Wieser et al 2013, Meija et al 2016.…”
mentioning
confidence: 99%